Anatomical variations of the cystic duct assessed by magnetic resonance cholangiopancreatography (MRCP): a cross-sectional study at tertiary center of Nepal - KC, Sudeep; Banjade, Udaya Raj; Ghimire, Prabeen (Journal of Patan Academy of Health Sciences, 2024)
Introduction: The cystic duct is a crucial structure that allows bile to flow from the gallbladder to the Common Bile Duct (CBD). Magnetic Resonance Cholangiopancreatography (MRCP) can accurately depict the cystic duct anatomy and its variants which can help surgeons and interventional radiologists tailor their approach to each patient’s unique anatomy and reduce the risk of inadvertent bile duct injury. The aim of this study was to evaluate variations of cystic ducts in patients undergoing MRCP.Method: This cross-sectional, prospective study was done in Department of Radiology, Patan Hospital. MRCP of 252 patients done between 1st September 2023 to February 2024 were analysed. The three-dimensional MRCP images were visually analysed and categorized as per the study done by Sarawagi et al. Statistical analysis was performed using SPSS (Statistical Package for the Social Sciences)20.Result: MRCP of patient were evaluated out of which were 99(39.29%) were males and 153(60.71%) were females. The most common type was right lateral insertion seen in 120(47.62%) patients and rest of patients having other anatomical variants. Posterior insertion in 36(14.29%) was most commonly seen variant followed by high insertion in 25(9.92%). Right posterior sectoral hepatic duct draining into the cystic duct was the least common.Conclusion: Typical lateral insertion was found in a 47.62% patients and common other variations were also noted in our study. Variations in the cystic duct are not uncommon. This study reinforces the importance of considering anatomical variations of the cystic duct whenever performing surgical, endoscopic and percutaneous procedures.